ELASTIC ANALYSIS OF TALL REINFORCED CONCRETE FRAMES ON ELASTIC SUB-BASE (Nigerian Journal of Technology, 2005)
Frames of high-rise structures act as load-bearing construction for these tall buildings. They carry and distribute load that are acting on them to their foundations. The distribution pattern of these load play a very important role in the behaviour of the frames. They are normally assumed as resting on rigid sub-base, compacted hard-core. This is not true. They usually deflect downwards. In actual sense they normally rest on elastic sub-base a situation that reflects reality on sites. The sub-base model on which the building is resting also contribute to the way the whole structure behave. This paper examines the winkler model and the behavior of 11storey Reinforced Concrete Frames resting on rigid sub-base and on elastic sub-base. The achieved results are very remarkable.